ANALYSIS AND DESIGN OF AN ANDROID-BASED PERSONALIZED SCIENCE LEARNING MOBILE APPLICATION FOR UPPER ELEMENTARY SCHOOL STUDENTS - Muhammad Ali Ikhsanudin; Iwan Setiawan Wibisono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The advancement of digital technology has significantly impacted the field of education, including science learning (IPA) at the elementary school level. Science plays a vital role in shaping students’ scientific understanding, critical thinking skills, and environmental awareness. However, traditional teaching methods still face various challenges, particularly for upper-grade elementary students, such as low learning interest, limited media, and diverse learning styles. This study aims to analyze the learning needs and design a personalized mobile learning application based on Android to support more effective and engaging science education. The research adopts a software engineering approach, involving stages of needs analysis, user interface design, and feature development tailored to students’ cognitive levels and learning preferences. The proposed application offers interactive materials, adaptive quizzes, and automatic feedback to promote self-directed learning. The analysis indicates that a personalized mobile learning platform can significantly enhance students’ motivation and comprehension in science subjects. Therefore, integrating IPA learning with mobile technology presents a promising solution to foster adaptive, flexible, and modern science education for elementary school students.